Mathematical methods for scientists and engineers - McQuarrie, Donald A. (University Science Books, 2003)
Intended for upper-level undergraduate and graduate courses in chemistry, physics, math and engineering, this book is also suitable as a reference for advanced students in the physical sciences. It is logically organised and full of problems that detail every step, making it exceptionally well adapted for self study as well as for course use. Pedagogy includes detailed problems and examples.